Effect of ocean currents on ship navigation in the east China sea. (1st August 2015) - Chen, Chen; Shiotani, Shigeaki; Sasa, Kenji
Abstract: Weather and ocean states such as ocean winds, ocean waves, and ocean currents can significantly affect ship navigation. To fully understand the current׳s effect on navigational fuel and time costs, especially in the case of strong western boundary currents such as the Kuroshio Current, an in-depth examination of how the Kuroshio Current quantitatively affects ships is needed. This article presents simulations, based on the Princeton Ocean Model (POM), in the North Pacific Ocean and focuses on the ocean surface current in the East China Sea (ECS). Then, several numerical simulations of ship navigation are conducted by utilizing a ship-maneuvering model known as the Mathematical Maneuvering Group (MMG). The results show that the POM model can generate a high-quality Kuroshio Current distribution that can be applied to conduct numerical simulations of ship navigation. Highlights: High-resolution Kuroshio Current data are generated for numerical simulations of ship navigation. Corresponding ship positions affected by the Kuroshio Current can be predicted quantitatively by the numerical simulations of ship navigation. The cost and time of ship navigation can be reduced based on the present method.